Enhancements of mechanical properties of friction stir welding for 6061 aluminum alloy by Friction Stir Processing (FSP) method. - Salman, Ali A.; Takak, Ayad M.; Resan, Kadhim K. (Basrah Journal for Engineering Sciences, 2014)
Friction stir processing is a new method of changing the properties of a metal through intense, localized plastic deformation ,this process mixes the material without changing the phase (by melting or otherwise) and creates a microstructure with fine, equiaxedgrains, It is used to improve the microstructural properties of metals. In this paper, the enhancement of mechanical propertiesof friction stir welding specimens at variable rotation speeds (1100, 1300 and 1500 rpm) with constant feed speed (60mm/min) for 6061-T6 aluminum alloy is studied by using the friction stir processing method at the same variable rotation speed and feed speed in order to transform a heterogeneous microstructure to a more homogeneous, refined microstructure. The best results of the welding line at the parameter 60 mm/min weld speed and 1300RPM rotation speed for the friction stir welding (FSW) and friction stir processing (FSP) where the efficiency reaches to 84.61% for FSW and 89.05% for FSP of the ultimate tensile strength of the parent metal.